Effects of copper oxide nanoparticles on tissue accumulation and antioxidant enzymes of galleria mellonella L - Sezer Tuncsoy, Benay (2020)
Effects of copper oxide nanoparticles (CuO NPs) were investigated in the midgut and fat body of Galleria mellonella. Fourth instar larvae were exposed to 10 µg Cu/L of CuO until becoming last instar larvae, and catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione-s-transferase (GST) and acetylcholinesterase (AChE) and metal accumulation were evaluated. Copper accumulation was observed in midgut and fat body tissues of G. mellonella larvae exposed to CuO NPs. CuO NPs increased CAT activities in midgut and fat body, while SOD activities were decreased. CuO NPs exhibited significant increases in GST activity in fat body, while no significant differences were observed in the midgut of G. mellonella larvae. AChE activity significantly decreased in the midgut of G. mellonella whereas there is no significant effect on fat body in CuO NPs exposed larvae. In overall, these findings demonstrate that tissue accumulation and oxidative stress that is countered by antioxidant enzymes occur when G. mellonella larvae exposed to environmental concentration of CuO nanoparticles.